BIOL-08. IGFBP2 PROMOTES TUMOR METASTASIS IN SHH MEDULLOBLASTOMA. (1st June 2021) - Kunhiraman, Haritha; Kenney, Anna
Abstract: Medulloblastoma (MB) is the most common pediatric brain malignancy. MB comprises 5 major subgroups known as WNT, SHH p53wt, SHH p53mut, Group 3 and Group 4. Among the four MB subgroups SHH group is the most dominant molecular subgroup in infants and adults. These tumors are proposed to arise from cerebellar granule neuron precursors (CGNPs), whose developmental expansion requires SHH signaling from the neighboring Purkinje neurons. Previous reports suggest that SHH group features a unique tumor microenvironment compared with other MB groups. Recently, we performed cytokine array analysis of culture media from different MB cell lines. Interestingly, our data showed increased levels of IGFBP2 produced by SHH MB cell lines compared to others. We confirmed these results using ELISA and Western blotting from 3 human SHH MB cell lines, and Smo/A1 mouse tumor cells. IGFBP2 is a member of IGFBP super family of proteins; it plays important roles in tumor cell proliferation, metastasis and drug resistance. We analyzed the role of IGFBP2 in SHH group medulloblastoma tumor growth and metastasis. IGFBP2 knock-down stable cell lines showed phenotypic changes including reduced cell proliferation, cell migration and colony size. Our preliminary in vitro data suggest IGFBP2 exerts it metastasis-promoting role in SHH MB by regulating the expression of EMT marker proteins such as N cadherin, slug etc. and matrix remodeling proteins like MMPs and TIMPs. We are currently performing functional studies in organotypic tumor slice cultures to validate these findings and establish IGFBP2 as a novel regulator of aggressive tumor growth and spread in SHH MB.